Sustainability of Return and Reintegration of Returnees in Bulgaria: Re-Emigration Index - Misheva, Mihaela; Getova, Antoaneta; Bakalova, Maria (Research Papers, 2021)
Migration processes have been increasingly attracting scientific and political attention, and in recent years the focus on the return and reintegration of returnees has intensified. The study focuses on the relationship between the sustainability of migrants’ return to Bulgaria and the reintegration of returnees. The main hypothesis is that problematic post-return reintegration may hamper the sustainability of return and encourage returnees to re-emigrate. Based on a discussion of the different understandings of return, its sustainability and the reintegration of returnees, a model for analyzing the relationship between the sustainability of return and the reintegration of returnees "at home" is built. Central to the model is the constructed "reintegration index“, which links post-return integration with the degree of readiness for re-emigration. Although the index is based on economic factors, other social and subjective factors related to the sustainability of returns have been taken into account too. The model and the index are used for analysis of empirical data from a nationally representative survey among returning migrants in Bulgaria. The analysis reveals that about 70% of returnees either have almost no reason to stay in Bulgaria (12.4%) or have a high probability of re-migration (56.3%). The results reveal target groups and factors against which sustainable return policies can be developed and targeted.